TAXATION AND ECONOMIC DEVELOPMENT IN NIGERIA - Adebowale Ogunsola (Malete Journal of Accounting and Finance)
Ineffective tax system can impact negatively on economic development. Therefore, this study investigated the influence of taxation on the economic development in Nigeria. The study adopted time series research method. The data used were obtained from secondary sources, which covered a period from 2015 to 2022. Using regression analysis, the study found that company income tax (CITX) and value added tax (VATX) positively and insignificantly influence real gross domestic product, however, the influence of education tax (EDTX) is negligible. Results also revealed that the influence of CITX on poverty index is negligible, while VATX and EDTX have negative and positive insignificant influence on poverty index respectively. Besides, findings revealed that CITX negatively and insignificantly influences life expectancy. While VATX positively and significantly influences life expectancy, the influence of EDTX is positive and insignificant. Moreover, results showed that CITX positively and insignificantly influences balance of trade, whereas the influence of VATX and EDTX is negative and insignificant. Furthermore, findings showed that company income tax positively and insignificantly influences unemployment rate. While VATX negatively and significantly influences unemployment rate, the influence of EDTX is negative and insignificant. It can be concluded that CITX, VATX and EDTX have tendency to improve some indicators of economic development, while they will likely impair other indicators. Therefore, it is recommended for government to ensure that revenue generated from taxation is judiciously expended on projects that will contribute positively to economic development.